Covid-19 Pandemic and Open Economy: Can it Influence the Stability of the Financial System in Sigeract Countries? - Rusiadi Rusiadi; Ade Novalina; Riri Trisia; Wydia Sijabat; Rosna B B (Universitas Dharma Wacana, 2022)
This study discusses the impact of Covid -19 and an open economy on financial system stability in the Six Global Foreign Exchange Rate Countriefree, thesee countries are Brazil, Mexico, Colombia, Russia, Argentina,and Indonesia. This study uses the simultaneous regression analysis method (2TLS) with testing using Eviews 10 and the Covid-19 impact differential test using SPSS. The results of simultaneous regression analysis show that exports and Inflation have a positive inelastic effect on financial system stability. In addition,direct investment and interest rates have a positive lasting impactt on financial system stability. The different assets show that there is no significant difference in Inflation in Brazil and Mexico, but interest rates have significant differences before and after covid-1; in Colombia, Russia, Argentina,and Indonesia, there are substantial differences in Inflation and interest rates before and after covid-19.